2013
DOI: 10.1590/s0103-73312013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Acesso a hospitais regionais de urgência e emergência: abordagem aos usuários para avaliação do itinerário e dos obstáculos aos serviços de saúde

Abstract: A perspectiva do usuário é imprescindível para o aprimoramento das políticas de saúde direcionadas à garantia dos princípios constitucionais da universalidade e integralidade. Este estudo descritivo-transversal teve como objetivo avaliar o acesso ao serviço de urgência e emergência em hospitais regionais de Pernambuco, com base no itinerário e nos obstáculos dos usuários até a assistência no referido setor. Selecionou-se uma amostra estratificada e aleatória, realizando-se 853 entrevistas semiestruturadas com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
23

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 14 publications
0
16
0
23
Order By: Relevance
“…Although some study participants felt that patients abuse the SUS by bypassing the established referral process and seeking care from specialists or emergency services on their own, the majority of focus group participants described patients as vulnerable, naïve systems users. A study conducted in seven Brazilian hospitals found that the majority of patient respondents (77.1%) resorted to hospitals as their first choice of health facility because of “absence of professionals” in their communities [32]. Our study participants related similar accounts of patients telling them they were sent to the hospital because doctors were not available in their HBUs.…”
Section: Discussionmentioning
confidence: 94%
“…Although some study participants felt that patients abuse the SUS by bypassing the established referral process and seeking care from specialists or emergency services on their own, the majority of focus group participants described patients as vulnerable, naïve systems users. A study conducted in seven Brazilian hospitals found that the majority of patient respondents (77.1%) resorted to hospitals as their first choice of health facility because of “absence of professionals” in their communities [32]. Our study participants related similar accounts of patients telling them they were sent to the hospital because doctors were not available in their HBUs.…”
Section: Discussionmentioning
confidence: 94%
“…All others addressed 'local-regional' issues. Half of all 'evaluation studies' discussed regionalization from the point of view of hospital care 53,65,76 , likely consisting of presentations of work performed by a team working on a line of research consistent with the reality in Pernambuco. Two other articles discuss the reality of the state of SP, and within the municipalities that make up metropolitan Sao Paulo respectively, and comprehensive care for chronic diseases 49,11 .…”
Section: Type 1 -"Practical" Articlesmentioning
confidence: 99%
“…A grande demanda nos serviços de PS também está relacionada à confiança dos usuários na assistência prestada pelo hospital somada a problemas da rede básica -tanto de resolutividade quando outros fatores como dificuldade para marcar consulta na UBS, ausência da necessidade de agendamento de consulta ou maior disponibilidade de recursos no serviço de pronto atendimento 17,18 . Os resultados do presente estudo, assim como a literatura nacional, mostram uma tendência hospitalocêntrica que continua sendo uma barreira a ser vencida nos serviços de saúde 17,18 .…”
Section: (Figura 1)unclassified